MEMBUMIKAN ILMU WARIS SEBAGAI SOLUSI KONFLIK ANTAR SAUDARA AKIBAT PEREBUTAN HARTA WARIS - Muhammad Basirrudin; Isfandayani Isfandayani; Ria Mariginingsih (An-Nizam, 2022)
Inheritance is property left by someone who has died, then the property is distributed to those who are entitled to receive it. In Islam, provisions regarding inheritance have been regulated, then it becomes a branch of science called inheritance science which contains discussions related to the provisions regarding inheritance. These provisions are regulated in order to create justice and benefit, not the other way around, namely conflicts and divisions between heirs. However, in reality, there are still many conflicts and divisions in society due to the distribution of inheritance. The activities carried out in this program are inheritance training which was attended by 23 youths from youth organizations in the North Bekasi area. The implementation of the program activity "Embracing Inheritance as a Solution to Conflicts Between Siblings Due to Conquest of Inheritance" Alhamdulillah gave a positive impact for participants who took part in inheritance training activities, they became aware of Islamic Shari'a regarding inheritance, the provisions that Allah has regulated in al-Qur'an, and they understand the importance of understanding and knowing inheritance in Islam, from its provisions to its wisdom. And in particular, there were some participants who were able to understand to the stage of calculating the distribution of inheritance.